2013
DOI: 10.1097/ta.0b013e318278956d
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation induced by a thoracic trauma alters the cellular composition of the early fracture callus

Abstract: Our results suggest that the systemic posttraumatic inflammation induced by a thoracic trauma disturbed the inflammatory balance during the early healing stage by altering the recruitment of inflammatory cells and cytokine expression locally at the fracture site and thus impaired fracture healing. These findings provide new insights in the pathomechanisms of impaired fracture healing in patients experiencing severe trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 32 publications
8
64
2
1
Order By: Relevance
“…In the BAL fluid, C5a and IL-6 were significantly enhanced in both genotypes (Table 3). The additional thoracic trauma did not influence the concentration of inflammatory mediators in the fracture hematoma (Table 3) but, according to our previous studies [14,15,19,24], increased the recruitment of neutrophils to the fracture site in WT mice (Fig 2). However, the osteoblast-specific overexpression of C5aR1 did not affect inflammatory parameters in the combined trauma model (Table 3, Fig 2).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…In the BAL fluid, C5a and IL-6 were significantly enhanced in both genotypes (Table 3). The additional thoracic trauma did not influence the concentration of inflammatory mediators in the fracture hematoma (Table 3) but, according to our previous studies [14,15,19,24], increased the recruitment of neutrophils to the fracture site in WT mice (Fig 2). However, the osteoblast-specific overexpression of C5aR1 did not affect inflammatory parameters in the combined trauma model (Table 3, Fig 2).…”
Section: Resultssupporting
confidence: 65%
“…We evaluated fracture healing in a model of uncomplicated isolated fracture and in a model of impaired healing by combining the fracture with an additional thoracic trauma, which is associated with local and systemic complement activation and severe inflammation [14,15]. We hypothesize that if osteoblasts were important target cells for C5a, fracture healing would be disturbed.…”
Section: Introductionmentioning
confidence: 99%
“…In a rat model it was shown that repair of a stabilized femoral osteotomy in the presence of acute systemic inflammation induced by chest trauma was associated with an increase in granulocytes and a decrease in macrophages during the early soft callus phase of healing [38]. In another study conducted in neutrophil-deficient mice it was concluded that this type of granulocyte was not involved in the disruption of bone repair leading to malunion in the presence of systemic inflammation [27].…”
Section: Introductionmentioning
confidence: 97%
“…7 Inflammation is an important regulator of bone regeneration. 8,9 Following fracture injury, there is an initial inflammatory response that has a crucial role in bone healing. 1,10 However, severe or prolonged inflammatory response leads to delayed healing or bone repair failure.…”
mentioning
confidence: 99%